Financial linkages in European equity and debt markets - Klare, Nicolas (2017)
This paper studies financial market linkages in Europe throughout the lifetime of the Euro. In considering the national equity and sovereign debt markets of the seven biggest economies in Europe, I find important developments in cross-country as well as cross-asset linkages. There is evidence for a revival of country-specific risk, causing a differentiation between riskier “peripheral” Euro area countries (Italy, Spain) and presumably safer “core” countries (Germany, the Netherlands). As a consequence, a “flight to safety” phenomenon can be observed. Interestingly, there is evidence that these “flight to safety” capital flows partially revert themselves in periods of relative stability in European financial markets.